2002
DOI: 10.1128/aem.68.12.6220-6236.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtype Analyses of Campylobacter spp. from Arkansas and California Poultry Operations

Abstract: Campylobacter isolates from diverse samples within broiler production and processing environments were typed by using flaA short variable region DNA sequence analysis. Sixteen flocks from four different farms representing two broiler producers in Arkansas and California were analyzed. Fourteen of the flocks (87.5%) were Campylobacter-positive; two remained negative throughout the 6-week rearing period. In general, multiple clones were present within a flock. Additionally, clones found within a flock were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 32 publications
8
83
1
1
Order By: Relevance
“…In the United Kingdom (5), Sweden (7), and the Netherlands (53), studies suggest that conventionally reared broiler flocks are predominantly colonized with a limited number (generally one to two) of C. jejuni subtypes. In contrast, in other countries, such as the United States (44,47,66) and Australia (100), multiple campylobacter strains are commonly isolated from broiler flocks. This may indicate either that in some countries, conventionally reared flocks are exposed to several sources potentially containing different campylobacter strain types or that there is a single source which contains multiple strain types.…”
Section: Prevalence Of Campylobacters In Broilersmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United Kingdom (5), Sweden (7), and the Netherlands (53), studies suggest that conventionally reared broiler flocks are predominantly colonized with a limited number (generally one to two) of C. jejuni subtypes. In contrast, in other countries, such as the United States (44,47,66) and Australia (100), multiple campylobacter strains are commonly isolated from broiler flocks. This may indicate either that in some countries, conventionally reared flocks are exposed to several sources potentially containing different campylobacter strain types or that there is a single source which contains multiple strain types.…”
Section: Prevalence Of Campylobacters In Broilersmentioning
confidence: 99%
“…C. jejuni can be recovered from both standing water and soils. Recently, genotyping techniques have shown that at least some of these environmental isolates, particularly those from standing water, recovered before flock positivity, had the same genotypes as isolates subsequently recovered from the broiler flock (47,68). Thus, clean and intact concrete aprons can reduce the risk of carrying in contaminated material.…”
Section: Sources Of Poultry Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to different studies, infection on chicken farms could enter the flock by vertical transmission from parent flocks , or by horizontal transmission via different sources (Pearson et al, 1993;van de Giessen et al, 1998;Petersen & Wedderkopp, 2001;Hiett et al, 2002;Hansson et al, 2007). Groundwater is frequently used as drinking water in poultry farms.…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention estimate that Campylobacter enteritis is a multibillion-dollar disease and that the consumption of poultry meet is a primary source of human infection (10).…”
Section: Discussionmentioning
confidence: 99%